Analisis Pengaruh Total Returns terhadap Tingkat Engagement Dosen Institut Teknologi Bandung - Wulandari, Purwanti; Gustomo, Aurik (Jurnal Manajemen Teknologi, 2011)
Human resources aspect is one of crusial support in applying 'tridharma perguruan tinggi', includes ITB. ITB human resources management as well, especially to the lecturer as intellectual asset, will provide great added value to ITB. The establishment of the ITB lecturers' engagement must be pursued continuously. This research aims to determine the effect of total returns which includes compensation, state/recognition, and development opportunities to ITB's faculty engagement. The study used questionnaire which is spread to the lecturers in 12 Faculty/School at ITB. Respondent selected by simple random sampling method. Multiple regression analysis was used to estimate and test the model. The result of this study showed that recognition as independent variable had significantly affected the level of employee engagement. Whereas, compensation and development opportunity variables did not significantly affect ITB's lecturer engagement. The effect of moderator, age and tenure showed by as long as age and tenure increase, employee engagement was raised equally to compensation measurement. Result indicated that age and tenure positively influenced relationships between compensation and employee engagement but did not affect the relationships between recognition and development opportunity with employee engagement.Keywords: employee engagement, total returns, compensation, recognition, development opportunity,ITB.